Sistem Pendukung Keputusan Pemilihan Pelanggan Terbaik Menggunakan Kombinasi Pembobotan Logarithmic Least Square dan MOORA - Rifaldo, Setiawan; Priandika, Adhie Thyo (Building of Informatics, Technology and Science (BITS), 2024)
The best customers are individuals or groups who not only transact frequently but also provide more value to the business through loyalty, positive feedback, and referrals to others. They typically show a high level of satisfaction with the product or service offered, potentially bringing in new customers and improving the company's reputation. Selecting the best customers is often faced with a variety of issues that can affect the accuracy and effectiveness of the process. One of the main problems that occurs is the lack of a model used in determining the best customers. The purpose of this research is to implement a system that is able to effectively and accurately identify the best customers by integrating the LLS weighting technique and the MOORA method. In addition, this study also aims to overcome the shortcomings of existing weighting and evaluation methods by integrating the two techniques, providing a more robust and adaptive solution in the context of data-based decision-making. The ranking results in determining the best customers obtained the result, namely Sabtoni occupies the first position with the highest score of 0.47344. Furthermore, Zahra is in second place with a score of 0.39815, followed by Tuty with a value of 0.39498 in third place.